2022
DOI: 10.3390/coatings12020226
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biodegradable Materials on the Quality of Plums

Abstract: Edible starch-based materials have shown a positive impact on quality parameters. In this study, plums (Prunus domestica cv. Jojo) were divided into five groups: a control, two coating treatments (starch and starch-whey protein (80–20%), and two film systems (starch and starch-whey protein (80–20%). Biodegradable packaging, particularly the coating treatment, had no negative effect on color parameters. After 28 days of performed tests, firmness was boosted with starch and starch-whey protein (80–20%) films. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…The minor changes in color parameters observed in coated samples suggests a delay in ripening associated with the barrier to gases exerted by the coating emulsions and correlates with the behavior observed in the analysis of fruit firmness, with higher values in coated than in control samples, indicating that the coatings effectively modified the plum respiration and ethylene production rates and slowed down the fruit's metabolism [50]. Similar results have been reported in plums coated with HPMC [8,24], chitosan and alginate [22,46,50], GA [23], and starch/whey protein [13,16]. In addition, some studies have also confirmed that the incorporation of essential oils improves the effect of some polysaccharide coatings, such as aloe vera gel, GA, and HPMC, on delaying plum ripening parameters such as color and firmness [8,17,23,51].…”
Section: Plum Peel Colorsupporting
confidence: 81%
See 2 more Smart Citations
“…The minor changes in color parameters observed in coated samples suggests a delay in ripening associated with the barrier to gases exerted by the coating emulsions and correlates with the behavior observed in the analysis of fruit firmness, with higher values in coated than in control samples, indicating that the coatings effectively modified the plum respiration and ethylene production rates and slowed down the fruit's metabolism [50]. Similar results have been reported in plums coated with HPMC [8,24], chitosan and alginate [22,46,50], GA [23], and starch/whey protein [13,16]. In addition, some studies have also confirmed that the incorporation of essential oils improves the effect of some polysaccharide coatings, such as aloe vera gel, GA, and HPMC, on delaying plum ripening parameters such as color and firmness [8,17,23,51].…”
Section: Plum Peel Colorsupporting
confidence: 81%
“…Thus, for example, biopolymer-lipid composite coatings did not reduce weight loss in apples [40], cherry tomatoes [41], table grapes [42], persimmon [43], and oranges [44,45], among others. In the particular case of plums, recent works have reported the inability of coating formulations based on alginate, chitosan, starch, whey protein, pectin, and carboxy methylcellulose to create an effective moisture barrier between the fruit and the environment [13,21,22], while other works have showed a positive effect of similar biopolymer-based coatings reducing plum weight loss [20,24,46]. These works illustrate the amount and complexity of factors that affect the barrier properties of edible coatings for a particular fruit.…”
Section: Plum Weight Lossmentioning
confidence: 98%
See 1 more Smart Citation
“…More recently, new methodologies have emerged. The application of edible coatings of natural origin, such as proteins and polysaccharides, or the use of biodegradable materials, such as starch, has proven to be effective in improving the plum postharvest characteristics [49,52,56,57]. These coating materials are safe and without implications for human health or negative influence on the environment, allowing the preservation of fruit with good quality characteristics for a longer storage period, reduce food waste and offer consumers high-quality plums with a longer shelf-life.…”
Section: Plums (Prunus Domestica L and P Salicina Lindl)mentioning
confidence: 99%